Nivel de conocimiento de los trabajadores de la facultad de agronomía en el uso de extintores ante casos de incendios. Iquitos. Loreto - Perú. 2021 - Ocmin Chavez, Cicelhy (2022)
This research aims to determine the knowledge level in the usage of fire extinguishers in the Faculty of Agronomy workers in the National University of the Peruvian Amazon in 2021. The research, by its approach, was quantitative, forward-looking strategy, with a general descriptive level and non-experimental research design. The target population was fifteen administrative workers (15), the same ones who were the sample of this research. All of them were at the time of implementation of the data-gathering instrument taking into account the inclusion and exclusion criteria. The technique used was the survey, and the tool applied was the ten-item questionnaire, which passed the validity (Aiken's validity index) and reliability (test of two halves) tests. The collected data was analyzed considering the research objectives and hypothesis, then expressed in a Basic Data Matrix (BDM) and analyzed, processed, and tabulated through the statistical package Statistical Product and Service Solutions (SPSS) version 25. The main results showed that 60% of the workers consider that the first thing to do is be qualified to use a fire extinguisher. However, 40% of them believe that it is not required. 80% of the workers did not answer correctly, also that it is false or they do not know whether class B or class C fire is extinct with water. Only 46.7% of the workers answered correctly regarding the first action to take when they see fire, compared to the 53.3% who did not. In the knowledge level about identification, control, and extinction of fire in the workplace, and their expertise handling fire extinguishers, the low level of knowledge prevails with 80%. Thus, rejecting the research hypothesis.